Straits settlements Blue Book (imports/exports) 1894-1895 vol.33-34 (Great Britain : Public Record Office, 1971)
Mengandungi'Recapitulatory and comparative statement of the value of imports into and exports from the Colony of the Straits Settlements for the year 1894';'Straits Settlements return of imports and exports for the year 1895';'Straits Settlements'; 'Colonial reports annual 1895'.